Modern agri-food systems, horticultural employment and women's empowerment - Katharina Krumbiegel; Miet Maertens; Meike Wollni (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
The transformation of global agri-food systems has led to the increased establishment of exportoriented horticultural plantations in developing countries. These labor intense production sites are associated with feminized employment patterns for the delicate handling of fruits and vegetables and therefore provide employment opportunities for women in rural areas. However, the social implications of these developments for women workers' roles in their households remain hardly understood. We address this research gap by assessing a wide range of indicators reflecting women's empowerment. We use primary survey data of 422 married households in Ghana, living in areas of large-scale pineapple plantations. We apply entropy balancing, a new re-weighting technique, and combine this with regression analysis. We find that female horticultural wage workers contribute a major share to the household's income, are more mobile, have better control over assets and reduced responsibilities in household chores. Women workers also report having more input into household decision-making.
Keywords: D13; J16; J43; 330; women's empowerment; horticultural employment; household decision-making